Epidemiology of adult Still's disease: estimate of the incidence by a retrospective study in west France. Issue 7 (July 1995) - Magadur-Joly, G; Billaud, E; Barrier, J H; Pennec, Y L; Masson, C; Renou, P; Prost, A
Abstract : OBJECTIVES–To estimate the incidence of adult Still's disease (ASD) and to specify, if possible, associated factors. METHODS–A retrospective study of the populations of the Brittany and Loire regions in west France was made from 1 January 1982 to 31 December 1991. All internal medicine and rheumatology practitioners of these regions were consulted. RESULTS–Sixty-two (62) cases were reported (93% response). The disease incidence calculated over five years was 0.16 per 100, 000 inhabitants in the study population. There was no sex bias (sex ratio 1.06 in ASD v 1.05 in the overall population. The mean age of the study population was 36 years, with two peaks of distribution at 15-25 and 36-45 years. A history of allergy was present in 23% of patients (n = 14). In two patients, it was possible to correlate an environmental allergen to exacerbation of ASD. CONCLUSION–The yearly incidence of ASD was estimated to be 0.16 per 100, 000 inhabitants. However, it was not possible to incriminate any infectious, toxic, or genetic factors in exacerbation of the disease.